2021
DOI: 10.1038/s41386-020-00938-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term alcohol consumption alters dorsal striatal dopamine release and regulation by D2 dopamine receptors in rhesus macaques

Abstract: The dorsal striatum (DS) is implicated in behavioral and neural processes including action control and reinforcement. Alcohol alters these processes in rodents, and it is believed that the development of alcohol use disorder involves changes in DS dopamine signaling. In nonhuman primates, the DS can be divided into caudate and putamen subregions. As part of a collaborative effort examining the effects of long-term alcohol self-administration in rhesus macaques, we examined DS dopamine signaling using fast-scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 67 publications
2
17
1
2
Order By: Relevance
“…Then a stainless steel twisted bipolar stimulating electrode (P1 Technologies) was placed on the tissue surface near the area of dLight expression. For simultaneous photometry-voltammetry recordings, carbon fiber electrodes (CFE) were fabricated as previously described (Salinas et al, 2016; Salinas et al, 2021) and placed in the tissue in the center of the recording region of interest under 4X magnification. Slices were then visualized with 40X objective (0.8 NA) and the field of view (∼180um x 180um) was adjusted so the stimulating electrode was just outside the field of view and the CFE was in the center of the field of view.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then a stainless steel twisted bipolar stimulating electrode (P1 Technologies) was placed on the tissue surface near the area of dLight expression. For simultaneous photometry-voltammetry recordings, carbon fiber electrodes (CFE) were fabricated as previously described (Salinas et al, 2016; Salinas et al, 2021) and placed in the tissue in the center of the recording region of interest under 4X magnification. Slices were then visualized with 40X objective (0.8 NA) and the field of view (∼180um x 180um) was adjusted so the stimulating electrode was just outside the field of view and the CFE was in the center of the field of view.…”
Section: Methodsmentioning
confidence: 99%
“…A mechanical shutter (Uniblitz V25) was used to limit exposure to fluorophore-exciting light to discrete periods and minimize photobleaching of the dLight between recordings. FSCV recordings were carried out as previously described (Sgobio et al, 2014; Salinas et al, 2016; Sgobio et al, 2019; Salinas et al, 2021). Briefly, a triangle wave form voltage was applied to the CFE beginning at -0.4V to +1.2V and back to -0.4V.…”
Section: Methodsmentioning
confidence: 99%
“…The emergence of hyperkatifeia after repeated opioid exposure is linked to a reduction in dopaminergic function ( Diana, 2011 ; Koob and Volkow, 2010 ). Withdrawal from chronic morphine exposure decreases dopamine release in the nucleus accumbens and dorsal striatum ( Ashok et al., 2017 ; Pothos et al, 1991 ; Salinas et al, 2021 ). We found that fentanyl IVSA reduced the spontaneous firing of SNc dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of ethanol to increase the concentration of DA in the mesolimbic system has been known since the late 1980s ( Imperato and Di Chiara, 1986 ). To date, the studies using animal models have provided advanced characterization of the DA implication in neurobiological effects of ethanol, while clinical studies have concurred with a clarification of the involvement of DA in AUD ( Charlet et al, 2013 ; Söderpalm and Ericson, 2013 ; Chen et al, 2018 ; Salinas et al, 2021 ). On the other hand, both animal and human studies have also demonstrated that dysregulation of the NE system, which is tightly linked with arousal and stress response, can also be a key component of the AUD pathophysiology ( Haass-Koffler et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%